CLIENT COMPANIES’ PERCEPTION TOWARDS CREDIT RISK OF PRIVATE SECTOR BANKS WITH REFERENCE TO ICICI, HDFC, AXIS BANK, IDBI, AND YES BANK - G, Sunitha; V, Venu Madhav (Indian Journal of Finance and Banking, 2022)
The banking sector at present is facing many issues; one among them is credit risk. A Credit risk is termed as an estimate or forecast of the default of a borrower failing to recover his interest amount or borrowed amount. Currently, the banker or the lender is at risk of recovering the interest amount and principal amount, increasing their recovery costs. The present study makes an attempt to know the awareness of customers towards credit risk of private sector banks. The research objective is to analyze the significant association between Client Company’s perceptions with a view to credit risk. The study explains the major variation between client company’s perspectives towards Indian private sector. The study explains about the impact of credit risk on banks profitability. The present study helps banks to prevail over the problem of credit risk. The study analysis the objectives of research, hypothesis formulated, research methodology, findings and conclusions are discussed. The secondary sources for the study are through the websites of banks, Journals and client company’s websites. Primary data has been gathered from 285 client companies using convenience random sampling technique from private sector banks. JEL Classification Codes: H32, Z33, E32, D21, C12, G21.